2014
DOI: 10.1016/j.anai.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of nasal and ocular allergies: the Allergies, Immunotherapy, and RhinoconjunctivitiS (AIRS) surveys

Abstract: Most patients took nonprescription medications for their allergy symptoms or were treated by general practitioners, who did not use allergy testing when diagnosing ARC. Most patients seen by allergist/immunologists and otolaryngologists were evaluated with allergy tests, and most allergen immunotherapy was provided by allergy specialists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 11 publications
0
31
0
1
Order By: Relevance
“…In The Allergies, Immunotherapy, and Rhinoconjunctivitis Survey (AIRS) performed in the US questioning health care providers who prescribe primarily SCIT, found that only about a third completed three years of immunotherapy [87]. A retrospective review evaluated US veterans' adherence to SCIT over a 10-year period [88].…”
Section: Adherence and Cost Issues: Scit Versus Slitmentioning
confidence: 99%
“…In The Allergies, Immunotherapy, and Rhinoconjunctivitis Survey (AIRS) performed in the US questioning health care providers who prescribe primarily SCIT, found that only about a third completed three years of immunotherapy [87]. A retrospective review evaluated US veterans' adherence to SCIT over a 10-year period [88].…”
Section: Adherence and Cost Issues: Scit Versus Slitmentioning
confidence: 99%
“…In 2014, the Allergies, Immunotherapy, and Rhinoconjunctivitis (AIRS) surveys concluded that depending on the specialty, the percentage of allergic rhinoconjunctivitis patients receiving AIT ranged from 7% to 33%. Amongst the adult patients, allergists/immunologists reported that 33% were undergoing AIT compared to the 25% reported by otolaryngologists . Not surprisingly, otolaryngologists share the role in provision of AIT with allergists/immunologists.…”
Section: Discussionmentioning
confidence: 74%
“…A lack of training in immunotherapy was the most common reason otolaryngologists and other physician specialties cited for not offering AIT—except for allergist/immunologists, who most often cited cost. While 95% of allergist/immunologists conducted an allergy test in office when diagnosing ARC, only 63% of otolaryngologists and 28% to 39% of the other physician specialties did so . Otolaryngologists who did conduct allergy tests in‐office when diagnosing ARC also provided immunotherapy in‐office.…”
Section: Discussionmentioning
confidence: 99%
“…The AIRS provider survey design is described in detail elsewhere . Healthcare providers were randomly selected from the American Medical Association (AMA) Master List and from national lists of optometrists, nurse practitioners, and physician assistants, and interviewed by telephone between February and May in 2012.…”
Section: Methodsmentioning
confidence: 99%